Algorithm for the cams synthesis for the slay mechanism drive - Podgornyj, Yu I; Yu Skeeba, V; Kirillov, A V; Maksimchuk, O V; Lobanov, D V; Martyushev, N V (Journal of physics. Conference series, 2021)
The paper presents an algorithm for the synthesis of the law of motion of the weft beat-up mechanism intended for the production of closely woven fabrics, which are currently manufactured mainly on shuttle looms. These machines have such disadvantages as significant dimensions, strong vibrations and noise during operation, as well as low performance. Shuttleless looms are devoid of such disadvantages. However, production of closely woven fabrics on such machines can face a number of problems, such as increased vibration, the machine tool turning off due to an increased beating-up strip and accelerated wear of mechanisms which, in turn, leads to a lower productivity and product quality. The conducted research allowed developing an algorithm for the synthesis of complex-profile cams of the slay mechanism drive. The use of the developed mechanism is theoretically proved and experimentally confirmed to provide the required performance and quality as well as to significantly expand the range of fabrics produced on STB shuttleless looms.